2016
DOI: 10.1074/jbc.m115.697292
|View full text |Cite
|
Sign up to set email alerts
|

PAK4 Methylation by SETD6 Promotes the Activation of the Wnt/β-Catenin Pathway

Abstract: Lysine methylation of non-histone proteins has emerged as a key regulator of many cellular functions. Although less studied than other post-translational modifications such as phosphorylation and acetylation, the number of known methylated nonhistone proteins is rapidly expanding. We have identified the p21-activated kinase 4 (PAK4) as a new substrate for methylation by the protein lysine methyltransferase SETD6. Our data demonstrate that SETD6 methylates PAK4 both in vitro and at chromatin in cells. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…FoxM1 methylation by SETD3 adds a new regulatory dimension to this complex process. As many non-histone proteins in the human proteome are known to be methylated2728293031323334, we hypothesize that additional cellular factors that regulate the VEGF signaling under hypoxia may also be methylated by SETD3. Interestingly, two of the known VEGF receptors35, FLT1 (VEGFR1) and KDR (VEGFR2), were identified as SETD3 interacting proteins in our ProtoArray screen (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FoxM1 methylation by SETD3 adds a new regulatory dimension to this complex process. As many non-histone proteins in the human proteome are known to be methylated2728293031323334, we hypothesize that additional cellular factors that regulate the VEGF signaling under hypoxia may also be methylated by SETD3. Interestingly, two of the known VEGF receptors35, FLT1 (VEGFR1) and KDR (VEGFR2), were identified as SETD3 interacting proteins in our ProtoArray screen (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear PAK4 has been found in endometrial cancer in postmenopausal women (Siu et al 2015). Recently, PAK4 has been shown to be methylated by lysine methyltransferase SETD6; and its interaction with SETD6 and β-catenin regulates β-catenin-target genes (Vershinin et al, 2016). Another PAK-signaling-mediated regulation of gene expression is PAK1 phosphorylation-dependent modulation of corepressor functions.…”
Section: Paks Nuclear Functionsmentioning
confidence: 99%
“…Lysine methylation may be important not only in epigenetic regulation of gene expression, but also in the regulation of cellular signal transduction pathways (Kurash et al, 2008;Van Duyne et al, 2008;Abu-Farha et al, 2011;Herz et al, 2013;Jakobsson et al, 2015;Zhang et al, 2015;Vershinin et al, 2016). During E. histolytica phagocytosis, an event related to its pathogenicity (Orozco et al, 1983), EhHKMT2 and EhHKMT4 were located around ingested erythrocytes and they colocalized and co-immunoprecipitated with EhADH, a protein involved in phagocytosis (Rodriguez et al, 1989;Garcia-Rivera et al, 1999), suggesting that these EhHKMTs could methylate some proteins that are implicated in this process.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications are catalyzed by lysine methyltransferases (HKMTs); and most of them contain a SET domain (Dillon et al, 2005), which was originally identified in Drosophila suppressor of variegation [Su(var)3-9] (Tschiersch et al, 1994), enhancer of zeste [E(z)] (Jones and Gelbart, 1993) and trithorax (Stassen et al, 1995). In addition to histones, HKMTs also target a broad range of other cellular proteins, suggesting that they contribute to the regulation of additional processes (Kurash et al, 2008;Van Duyne et al, 2008;Abu-Farha et al, 2011;Jakobsson et al, 2015;Zhang et al, 2015;Vershinin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%